Ihdad for Career Women in the Perspective of Maslahah mursalah (Study of the Fatwa of the Indonesian Ulema Council Number 11 of 1981) - Nasution, Saipul; Kanggas, Fazari Zul Hasmi; Rachmawati, Andini; Diana, Rashda; Hasanah, Nur (Ijtihad, 2024)
**English**There are some restrictions for a woman who is in iddah, these restrictions are known as ihdad. Ihdad can be in the form of: not allowed to adorn and leave the house. In the Indonesian context, the provisions of ihdad are regulated in MUI Fatwa No.11 of 1981 concerning the iddah of death, which basically states that, firstly, whether or not it is permissible for a woman who is in iddah to leave the house is a matter of khilafiyyah, secondly, the opinion of the majority of scholars is that it is not permissible for a woman in iddah to leave the house at night, even if it is to perform the pilgrimage. In this case, the fatwa needs to be reviewed, especially its relevance for career women who are experiencing the iddah period. Because according to the author, the provisions in the fatwa have been considered long enough and are not in accordance with the increasingly advanced situation as it is now. And the method of legal istinbath Maslahah mursalah in this study is used as a review tool in the Fatwa, whether the fatwa is in accordance with the provisions set forth in Maslahah mursalah.   The result of this research is that the concept of ihdad described by the decree of Fatwa of the Indonesian Ulema Council No.11 of 1981 is by not being allowed to leave the house during the day and night, even though it is to perform the pilgrimage. However, if there is an urgent need then it is allowed to leave the house. With the analysis of Maslahah mursalah, MUI's fatwa on iddah of death which is intended for ihdad of career women is in accordance with Maslahah mursalah, because the fatwa has fulfilled the criteria or conditions described by Maslahah mursalah.                                                                                **Indonesia**There are some restrictions for a woman who is in iddah, these restrictions are known as ihdad. Ihdad can be in the form of: not allowed to adorn and leave the house. In the Indonesian context, the provisions of ihdad are regulated in MUI Fatwa No.11 of 1981 concerning the iddah of death, which basically states that, firstly, whether or not it is permissible for a woman who is in iddah to leave the house is a matter of khilafiyyah, secondly, the opinion of the majority of scholars is that it is not permissible for a woman in iddah to leave the house at night, even if it is to perform the pilgrimage. In this case, the fatwa needs to be reviewed, especially its relevance for career women who are experiencing the iddah period. Because according to the author, the provisions in the fatwa have been considered long enough and are not in accordance with the increasingly advanced situation as it is now. And the method of legal istinbath Maslahah mursalah in this study is used as a review tool in the Fatwa, whether the fatwa is in accordance with the provisions set forth in Maslahah mursalah.   The result of this research is that the concept of ihdad described by the decree of Fatwa of the Indonesian Ulema Council No.11 of 1981 is by not being allowed to leave the house during the day and night, even though it is to perform the pilgrimage. However, if there is an urgent need then it is allowed to leave the house. With the analysis of Maslahah mursalah, MUI's fatwa on iddah of death which is intended for ihdad of career women is in accordance with Maslahah mursalah, because the fatwa has fulfilled the criteria or conditions described by Maslahah mursalah.